The impact of cultural interaction on the effectiveness of muslimah da'wah communication in Indonesia - Ulfa, Fadillah; Solihu, Abdul Kabir Hussain; Saari, Che Zarrina (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2025)
Purpose – The study is to explore how cultural factors influence the delivery and reception of Islamic teachings by Muslimah da’wah practitioners and the communities they engage with. Method – This study employs a qualitative research design, collecting data through in-depth interviews with Muslimah da'wah activists, community leaders, and recipients of da'wah messages in various regions of Indonesia. The study found that cultural values and traditions significantly shape the way da'wah messages are communicated and accepted, with regional variations influencing the effectiveness of these communications. Result - The results indicate that Muslimah da'wah practitioners who incorporate local cultural elements into their messages are more successful in engaging their audiences. This study emphasizes the significance of cultural sensitivity in da'wah practices and provides valuable insights into enhancing the effectiveness of Muslimah da'wah in Indonesia. The findings suggest that understanding and adapting to cultural contexts is essential for improving communication strategies in religious outreach. Implication – The implications of this research are significant for both da’wah practitioners and scholars of Islamic communication, emphasizing the need for a culturally informed approach to religious communication. Originality / Value – The study examines the impact of cultural interaction on the effectiveness of da'wah in Indonesia, providing unique insights into how cultural factors influence Muslimah da'wah communication strategies and highlighting the importance of cultural sensitivity in religious outreach. *** Tujuan – Penelitian ini bertujuan untuk menggali bagaimana faktor budaya memengaruhi penyampaian dan penerimaan ajaran Islam oleh para praktisi da’wah Muslimah serta masyarakat yang mereka jangkau. Metode – Penelitian ini menggunakan desain penelitian kualitatif, dengan pengumpulan data melalui wawancara mendalam dengan aktivis da’wah Muslimah, pemimpin komunitas, dan penerima pesan da’wah di berbagai daerah di Indonesia. Penelitian ini menemukan bahwa nilai dan tradisi budaya secara signifikan membentuk cara pesan da’wah disampaikan dan diterima, dengan variasi regional yang memengaruhi efektivitas komunikasi tersebut. Hasil: Hasil penelitian menunjukkan bahwa praktisi da’wah Muslimah yang mengintegrasikan unsur-unsur budaya lokal dalam pesan mereka lebih berhasil dalam melibatkan audiens mereka. Penelitian ini menyoroti pentingnya sensitivitas budaya dalam praktik da’wah dan memberikan wawasan berharga untuk meningkatkan efektivitas da’wah Muslimah di Indonesia. Temuan ini mengindikasikan bahwa pemahaman dan penyesuaian terhadap konteks budaya sangat penting untuk memperbaiki strategi komunikasi dalam penyuluhan agama. Implikasi – Implikasi dari penelitian ini sangat signifikan bagi praktisi da’wah dan akademisi komunikasi Islam, dengan menekankan perlunya pendekatan komunikasi agama yang peka terhadap budaya. Orisinalitas / Nilai – Penelitian ini menggali dampak interaksi budaya terhadap efektivitas da’wah di Indonesia, memberikan wawasan unik tentang bagaimana faktor budaya membentuk strategi komunikasi da’wah Muslimah dan menekankan pentingnya sensitivitas budaya dalam penyuluhan agama.